Nutritional Support Of The Elderly Patient: The Role Of The Nurse - Hanan Bader Alanzi , Zeinah Turki Algahtani , Maha Hmoud Alenazy , Rajsa Nasar Al Doseri , Ashwaq Mubarak Nasser , Nowayer Mohammad Al-Dosari , Nora Mubark Nasser Al-Dosari , Renad Mohammad Qasem Algahtani (Migration Letters, 2022)
The advent of dietary supplements has meant that individuals do not need to rely solely on foods to provide the essential nutrients for health (1). Dietary supplements are widely available to consumers worldwide and use of these products has significantly increased during the past two decades (2).